Heterotrophic components of soil respiration in pastures and forests in southwestern Amazonia, Acre, Brazil - Eric Atlas Davidson (Revista Ambiente & Água, 2008)
In this paper we present data on soil microbial biomass and heterotrophic respiration in pastures, mature and secondary forests, in order to elucidate their contribution to total CO2 flux from soil to atmosphere. The research was conducted in Southwestern Amazonia, Acre State, Brazil. Microbial biomass was estimated using a variation of the traditional fumigation-extraction method and heterotrophic respiration was measured using respirometry flasks attached to an infrared gas analyzer. Soil microbial biomass and heterotrophic respiration did not differ statistically among pastures, mature and secondary forests. These laboratory results indicate that higher CO2 fluxes from pasture soils measured in situ are probably due to higher root respiration by pasture grasses.